The Semantic Shift of War: A Comparative Analysis of Political Discourse on the Gaza Conflict across News, Speech, and Social Media - Sutarman Sutarman; Zainudin Abdussamad (JURNAL PENDIDIKAN BAHASA, 2025)
This study investigates the rapid semantic shifts of political terminology within the context of the 2025 Israel-Gaza conflict. Grounded in the cognitive-functional frameworks of Blank and Traugott and Dasher, the research analyzes how lexical meaning is constructed and altered across three distinct registers: international news media (Al Jazeera), diplomatic speech (UN Secretariat), and institutional social media (UN Human Rights). Using a qualitative descriptive approach, 15 key lexicons were analyzed to identify patterns of semantic change, including broadening, narrowing, and pejoration. The findings reveal three divergent trajectories of meaning: (1) Institutional Specialization in diplomatic speech, where general ethical terms like accountability are narrowed into performative legal demands; (2) Pragmatic Broadening in news media, where technical terms like ceasefire expand to encompass complex humanitarian narratives; and (3) Emotive Intensification on social media, where descriptive phrases undergo hyperbolic shifts to mobilize digital publics. The study concludes that political conflict acts as a catalyst for semantic change, driven by the opposing forces of institutional need for legal precision and the media’s drive for affective impact. These results support the view that semantic change is fundamentally discourse-driven and highly sensitive to the communicative affordances of the platform.